Disabilitas Sebagai Pengamat Pemilu Perspektif Fiqh Siyasah (Studi Bawaslu Padang Panjang) - hendri hendri; chairunnisa chairunnisa (Politik Islam, 2023)
The article that the author conducted regarding the Fiqh Siyasah Perspective on the Rights of Disabilities to Become Election Supervisors in Law Number 8 of 2018 (Kota Padang Panjang) allows people with disabilities to become election supervisors. However, only by providing accessibility, which is an easy way for persons with disabilities to achieve equal opportunities to obtain the same status, rights and obligations, equality of status can be realized. Therefore, it is necessary to make efforts to provide accessibility for persons with disabilities. It is hoped that with these efforts, persons with disabilities can be totally integrated in realizing national development goals in general and improving their social welfare in particular. This variety of persons with disabilities has different difficulties and problems. Different difficulties and problems need various solutions. In Law number 7 of 2017 concerning general elections it has been explained that persons with disabilities have the same rights as others to be elected or vote. Whereas in Law No. 8 of 2016 it is emphasized again that in Article 13 letter (f) disabilities have their rights in politics to become organizers in elections. This study aims to find out how the practice of Law No. 8 of 2016 regarding the right to disability to become election supervisors and find out from the siyasa fiqh aspect. At this writing, it examines the facts that are in Bawaslu and this really happened in the Bawaslu realm. The author can conclude that disability rights are still not given enough attention when it comes to their political rights to become election supervisors